Penerapan Self Determination Theory: Peran Dukungan Orangtua Terhadap Academic Buoyancy Siswa Menjalani Pembelajaran Jarak Jauh - Meilani Rohinsa; Gianti Gunawan; Anissa Lestari Kadiyono (Universitas Islam Tribakti Lirboyo Kediri, 2021)
The Covid-19 pandemic has made students unable to carry out the teaching and learning process as usual. There are restrictions on physical meetings and the implementation of the emergency curriculum. It creates challenges and learning problems for students. It takes the ability to overcome it or what is known as academic buoyancy. The study aims to examine the role of parents in the academic buoyancy of students undergoing distance learning from the point of view of self-determination theory. Participants in this study were 215 students aged 12-15 years. The measuring tools in this study were the Parents as Social Context Questionnaire and the Academic Buoyancy Scale. The results show that each dimension of parental support and the three dimensions simultaneously have a role in shaping the ability to overcome academic barriers or academic buoyancy in children. The results of this study imply the importance of support from parents in the form of autonomy support, structure and involvement in shaping children's abilities to overcome academic barriers or academic buoyancy.